Mentoring bagi para Mediator Hubungan Industrial sebagai suatu Intervensi Pengembangan Kompetensi Sumber Daya Manusia - Wustari L. Mangundjaya (Journal on Education, 2024)
In business, a harmonious relationship among the owner, management, and employees is ideal and needed by all parties. However, in reality, this condition cannot always be achieved. Many variables might hinder this harmonious relationship, such as misunderstanding, different perceptions, and different needs that consequently affect the relationship, and even this relationship needs a mediator to mediate the relationship. In this regard, mediator play an essential role and consequently require special skills to conduct their roles professionally. Meanwhile, not every mediator has mastered the roles that need an intervention program to develop the needy skills. In this regard, mentoring was chosen as the intervention program for the Industrial Relation Mediator who works at the Ministry of Manpower Republic Indonesia from many regions in Indonesia. This mentoring program was done in three stages with different objectives and methods. Evaluation results showed that participants were satisfied with the program.